Optimizing zakāt management as an effort to alleviate poverty: A case study at the Central Java Baznas - Fita Nurotul Faizah (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2022)
Purpose – research this aim for knowing how much far ZIS management at BAZNAS Central Java Province as a effort alleviation poverty in Central Java.Methods in _ study this is descriptive qualitative through studies library.Result – Zakat, Infaq and Shodaqoh (ZIS) play a role in prevention to accumulation wealth to a few. _ Like zakat, which obliges the rich to pay distribute treasure his wealth to group of poor and needy people. Collecting ZIS at BAZNAS Central Java Province individually effective capable Becomes potential source of funds for relieve poverty as well as increase quality source power Human Resources (HR) of Central Java Province is appropriate with the ZIS distribution model, namely consumptive nor productive.Implication – research this conducted for Becomes consideration, evaluation and alternative strategies on zakat management in Baznas Central Java Province.Originality - Authenticity study this lies in the object under study, analysis, and location research .